A study of 853 high grade osteosarcomas from a single institution—Are outcomes in Indian patients different?. Issue 2 (22nd August 2017) - Puri, Ajay; Byregowda, Suman; Gulia, Ashish; Crasto, Saniya; Chinaswamy, Girish
Abstract : Aims: To review outcomes of 853 patients of primary high grade osteosarcoma operated with curative intent between January 2006 to December 2013. Methods: All patients underwent appropriate surgical resection after preoperative chemotherapy (non methotrexate based). Excised specimen was analyzed for margins and response to chemotherapy. We analysed various factors (sex, age, size, site, type of surgery, pathologic fractures, margin status, and chemotherapy induced necrosis) for their impact on outcomes. Results: Five year overall survival (OS) for entire cohort was 49% and event free survival (EFS) was 42%. Seventy hundred thirty‐eight non metastatic patients had OS of 53% and EFS of 47% at 5 years. The 3 year OS and EFS of the metastatic patients was 22% and 9%, respectively. Analysis of 738 non metastatic patients demonstrated that chemotherapy induced necrosis, size of tumor (< / >8 cms), type of surgery (limb salvage vs amputation) significantly affected overall survival. Local recurrence was 9%. Site of tumor (long bone vs pelvis), type of surgery and chemotherapy induced necrosis influenced local recurrence. Conclusions: Our patients appeared to have poorer survival compared to most Western data, possibly attributable to large tumors. In contrast to existing data, males (71%) were predominantly affected and only patients with 100% necrosis qualified as good responders regarding OS.